Fine-tuning zeolite pore structures with carbon coating for enhanced gas separation in polyimide-based mixed matrix membrane - Triyanda, Gunawan; Nurul Widiastuti, .; Alvin Rahmad, Widyanto; Hamzah, Fansuri; Syafsir, Akhlus; Wan Norharyati, Wan Salleh; Ahmad Fauzi, Ismail; Norazlianie, Sazali; Lin, Rijia; Motuzas, Julius; Smart, Simon (Elsevier Ltd, 2024)
Impregnated zeolite-carbon (IZC), also known as pore-modified zeolite, was used as a potential filler in a P84 co-polyimide-based hollow fiber mixed matrix membrane (HF MMM) to enhance gas separation. The presence of carbon structure on the zeolite framework pore was to avoid the trapped moisture that could lead to permeability reduction. This work seeks to investigate the impact of IZC addition (0.5, 1.0, and 1.5 wt%) to the P84 membrane and examine its permeability and separation performance. Adding IZC filler to the P84 membrane generates the enhancement of gas selectivity and permeability. The optimal enhancement was observed at 1 wt% of IZC loading, in which selectivity of CO2/CH4, CO2/N2, O2/N2, H2/N2, and H2/CH4 was enhanced by 50.506, 51.042, 5.693, 16.712, and 16.338%, respectively. On the other hand, H2, CO2, and O2 permeability at the loading were improved from 11.182 to 26.761, from 4.683 to 14.501, and from 1.637 to 3.546 Barrer, respectively. The improvement of gas selectivity was contributed by the presence of carbon in the zeolite framework, providing a molecular sieving effect while tuning carbon properties with pore regularity by templating in the zeolite framework enhances the gas permeability.